Affinity label for beta-adrenergic receptor in turkey erythrocytes. - Atlas, D (1976)
The compound N-[2-hydroxy-3-(1-naphthoxy)-propyl]-N'-bromoacetylethylenediamine (NHNP-NBE) was found to label covalently the beta-adrenergic receptor in turkey erythrocytes. The compound inhibits irreversibly 1-epinephrine-dependent adenylate cyclase activity [ATP pyrophosphate-lyase (cyclizing), EC 4.6.1.1] in the whole turkey erythrocyte as well as in the erythrocyte membranes possessing the beta-receptor. The affinity label blocks, also irreversibly, the specific [3H] propranolol binding, whereas other bromoacetyl compounds tested have no effect on binding, even at high concentrations, which cause enzyme inactivation. 1-Epinephrine and propranolol offer protection against the affinity label in whole turkey erythrocytes as well as in membranes prepared from these cells. The potential usefulness of an irreversible beta-antagonist is discussed.